Linguistic Context in Verb Learning: Less is Sometimes More. Issue 1 (2nd January 2020) - He, Angela Xiaoxue; Kon, Maxwell; Arunachalam, Sudha
ABSTRACT: Linguistic contexts provide useful information about verb meanings by narrowing the space of candidate concepts. Intuitively, the more information, the better. For example, "the tall girl is fezz ing, " as compared to "the girl is fezz ing, " provides more information about which event, out of multiple candidate events, is being labeled; thus, we may expect it to better facilitate verb learning. However, we find evidence to the contrary: in a verb learning study, preschoolers (N = 60, mean age = 38 months) only performed above chance when the subject was an unmodified determiner phase, but not when it was modified (Experiment 1). Experiment 2 replicated this pattern with a different set of stimuli and a wider age range (N = 60, mean age = 45 months). Further, in Experiment 2, we looked at both learning outcomes—by evaluating pointing responses at Test, and also the learning process—by tracking eye gaze during Familiarization. The results suggest that children's limited processing abilities are to blame for poor learning outcomes, but that a nuanced understanding of how processing affects learning is required.